The turtle's beating heart : one family's story of Lenape survival - Low, Denise (University of Nebraska Press, 2017)
"Denise Low recovers the life and times of her grandfather, Frank Bruner (1889-1963), whose expression of Lenape identity was largely discouraged by mainstream society."--Provided by publisher.